Analytical expression for total Base Transit Time in Epitaxial Bipolar Transistors - Khandoker, Ahsan Habib (1999)
The base width of a Bipolar Junction Transistor in an integrated circuit is very small and recombination within the base can safely be neglected. In most of the works on Base Transit Time with reverse biased collector junction the expressions for transit time have been derived separately for high injection and low injection condition of operations. But in this work we have obtained a new analytical expression for Base Transit Time with reverse biased collector junction that can be applied for all levels of injections. The results obtained by using the new formulation are in good agreement with numerical results available in the literature. In the second part of this work, the Base Transit Time with collector junction forward biased is studied. When the collector junction is forward biased, the base is extended into the collector. Under this situation total transit time is the time taken by electron to traverse base and also the injection region of the collector. Recent works have shown that the collector minority carrier lifetime is finite. Therefore, recombination current in the collector minority carrier lifetime is finite. Therefore recombination current in the collector cannot be neglected. Considering drift and diffusion current and recombination, expressions for collector transit time with forward biased collector junction are obtained for quasi- and hard-saturation regions of operation. The results are compared with those obtained without recombination. The two results are deviated significantly from each other. The transit time is found strongly dependent upon collector minority carrier lifetime. When the effective surface recombination velocity is not infinite, the charge storage in collector is large and transit time increases with current.